Pengaruh Social Support dan Self-Compassion Terhadap Loneliness pada Individu Dewasa Awal dengan Keluarga Bercerai - Mega Fazriaturohmah; Puspa Rahayu Utami Rahman; Dinda Aisha (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Loneliness is a subjective condition that arises when there is a mismatch between the social relationships an individual expects and those they actually experience. This study aims to investigate the influence of social support and self-compassion on loneliness among young adults from divorced families. The method used is a quantitative approach employing a causal design. The sample selection in this study employed a snowball sampling technique, involving 385 participants in Karawang Regency. The instruments used were the Multidimensional Scale of Perceived Social Support (MSPSS), Self-Compassion Scale (SCS), and UCLA Loneliness Scale (Version 3). Data analysis was conducted using multiple linear regression analysis. The significance value of the partial test for social support was 0.003 and for self-compassion < 0.00, indicating that social support and self-compassion have a significant partial and simultaneous effect on loneliness. On the other hand, the simultaneous test results showed a significance value of less than 0.00. Meanwhile, the coefficient of determination (R²) values indicate that social support contributes 4.00% and self-compassion contributes 6.30% to the loneliness variable. In other words, the two independent variables simultaneously contribute 10.3% to loneliness, while the remaining 89.7% is influenced by other variables outside the scope of this study.